2013
DOI: 10.1155/2013/242513
|View full text |Cite
|
Sign up to set email alerts
|

PKM2, a Central Point of Regulation in Cancer Metabolism

Abstract: Aerobic glycolysis is the dominant metabolic pathway utilized by cancer cells, owing to its ability to divert glucose metabolites from ATP production towards the synthesis of cellular building blocks (nucleotides, amino acids, and lipids) to meet the demands of proliferation. The M2 isoform of pyruvate kinase (PKM2) catalyzes the final and also a rate-limiting reaction in the glycolytic pathway. In the PK family, PKM2 is subjected to a complex regulation by both oncogenes and tumour suppressors, which allows f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
167
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(177 citation statements)
references
References 106 publications
(171 reference statements)
5
167
1
4
Order By: Relevance
“…Moreover, rescuing p53 in LFS-derived stromal cells led to inhibition of HIF-1␣ levels. PKM2 is a key mediator of the Warburg effect, the phenomenon by which proliferating cells alter their mode of energy production from oxidative phosphorylation to aerobic glycolysis, and its expression is increased in cancer cells (35,36). Although the metabolic function of PKM2 is well established, our findings support a role for this protein as a regulator of gene expression via direct interactions with HIF-1␣.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, rescuing p53 in LFS-derived stromal cells led to inhibition of HIF-1␣ levels. PKM2 is a key mediator of the Warburg effect, the phenomenon by which proliferating cells alter their mode of energy production from oxidative phosphorylation to aerobic glycolysis, and its expression is increased in cancer cells (35,36). Although the metabolic function of PKM2 is well established, our findings support a role for this protein as a regulator of gene expression via direct interactions with HIF-1␣.…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, decreased expression of c-myc and cyclin D1 were also observed in present study ( Figure 6F). This reason may be that different dosages and treating time of have different effects on the proliferation of some cell lines, PKM2 is a key glycolytic enzyme that regulates the Warburg effect and is necessary for tumor growth (Wong et al, 2013). Recent studies indicated that nuclear PKM2 could activate gene transcription and cell proliferation in human glioblastoma, prostate cancer and breast cancer cells (Gao et al, 2012;Lee et al, 2008;Luo et al, 2011a;Luo et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…6d). Thus, the ratio of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] ]CO 2 to [6-14 ]CO 2 was decreased (Fig. 6e).…”
Section: Pim2 Promotes Pkm2-dependent Glycolysis and Reduces Mitochonmentioning
confidence: 99%
“…Because PKM2 has a lower enzymatic activity compared with PKM1, it will channel more glycolytic intermediates into building blocks, such as nucleic acids, amino acids, and lipids, to support cancer cell proliferation. The enzymatic activity of PKM2 is under the control of metabolic intermediates, oncogenes, and growth factors (6). Growing evidence indicates that oncogenes reprogram glycolysis, impacting the tumor aggressive phenotype via regulating PKM2 (7).…”
mentioning
confidence: 99%